Responses of Tetragonula sapiens and T. clypearis to biotic and abiotic factors in Central Lombok, Indonesia - LUTFI ANGGADHANIA; KANTI DEWI RIZQIANI; KRISNAWATI KRISNAWATI; EKA NOVRIYANTI; YELIN ADALINA (Smujo International, 2026)
Abstract. Anggadhania L, Rizqiani KD, Krisnawati, Novriyanti E, Adalina Y. 2026. Responses of Tetragonula sapiens and T. clypearis to biotic and abiotic factors in Central Lombok, Indonesia. Asian J Agric 10 (1): g100157. https://doi.org/10.13057/asianjagric/g100157. Tetragonula spp. meliponiculture in Indonesia's dry tropical regions faces significant challenges from biotic and abiotic variables. This comparative study evaluated the responses of Tetragonula sapiens and T. clypearis to temperature, humidity, food availability, and pest occurrence in Central Lombok, Indonesia. Seventy colonies (35 per species) were monitored monthly for five months (July-November 2018) in two shaded demonstration blocks under managed conditions. Colony weight change (ΔW) was quantified as a proxy for colony development, while ambient temperature, relative humidity, and floral abundance were recorded concurrently. Multiple Linear Regression (MLR) analyses explored associations between ΔW and environmental variables at the block level (n = 5 monthly means per species), and separate simple regressions were fitted for each species. Colony weight change showed species-specific associations with environmental variables. Across both species, ambient temperature exhibited a stronger statistical association with ΔW than relative humidity. However, these relationships were based on a very small number of monthly observations and should be interpreted as exploratory. T. clypearis showed steeper negative associations with increasing temperature and decreasing relative humidity than T. sapiens, suggesting greater sensitivity to microclimatic variation within the observed range. In contrast, food availability was more strongly associated with colony weight dynamics in T. sapiens (R² = 0.819) than in T. clypearis (R² = 0.496). Pest inspections identified Psocoptera (Tapinella sp.) in the hives, marking the first documented case of this species in Central Lombok, associated with propolis discoloration and fungal growth. Within the limitations of the small dataset and the block-level design, microclimate and food availability were strongly associated with colony development in Tetragonula spp., during the dry season. These results highlight the importance of integrated floral, microclimate, and pest management for sustainable meliponiculture in Central Lombok.